Changes in aerodynamics during vocal cord dysfunction - Frank-Ito, Dennis O.; Schulz, Kristine; Vess, Gina; Witsell, David L. (Computers in biology and medicine, 2015)
Changes in laryngeal airflow dynamics during episodes of vocal cord dysfunction (VCD) have not been well described. Very little is known about how inspiratory airflow is impacted when the vocal cords transition from normal inhalation state to a paradoxical adducted state; and how much change in laryngeal airflow and resistance occur before symptoms of stridor and air hunger emerge. This study provides new insight on the effects of VCD on respiratory airflow using computational fluid dynamics (CFD) techniques. Computed tomography images of a subject with normal vocal cords opening at the time of scanning were digitally modified to mimic an episode of VCD. To quantify and compare changes in inspiratory flow during VCD attack and normal inhalation, steady-state, laminar simulations were performed for three different breathing rates. Pressure-flow analysis during VCD revealed that increasing inspiratory effort is not as efficient as in normal inhalation. Airflow resistance at the epiglottis was higher in the normal state (0.04Pa.s/mL versus 0.02Pa.s/mL) than in VCD; while resistance at the glottis and trachea remained roughly the same (0.04Pa.s/mL) during normal inhalation, it escalated during VCD (0.11Pa.s/mL and 0.13Pa.s/mL at the glottis and trachea, respectively). Peak airflow velocity and vorticity occurred around the glottis during VCD, and at the epiglottis during normal inhalation. This pilot study demonstrates that attempting to force more inspired air will yield greater glottal resistance during VCD. Furthermore, there were evidence of abrupt laryngeal pressure gradient, chaotic airflow and high concentration of shear stresses in the glottal region. •At different inhalation rate, mass flow rate in the normal cavity more than doubles flow in the VCD cavity•Visualization results showed a much slower flow above the glottal region in the VCD cavity than in the normal cavity•During episodes of VCD trying to increase inspiratory pressure so as to inhale more air may result in greater glottal resistance.